Association of Microcirculation Parameters with Mortality in Patients with Coronary Artery Disease Combined with COVID-19 - Vasyl Z. Netiazhenko; Serhii E. Mostovyi; Vitalii G. Gurianov (Український журнал серцево-судинної хірургії)
The aim. To investigate the association of microcirculation parameters with deaths in patients with coronary artery disease and COVID-19.